IMPACT OF Aerva javanica SUPPLEMENTATION DIET ON THE GROWTH, DIGESTIVE ENZYME ACTIVITY AND BODY BIOCHEMICAL COMPOSITION OF Labeo rohita FINGERLINGS - KUMARAN, S. ANANDA; DEVI, P. S. ARUNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The present work was carried out to study the impact of Aerva javanica on growth, digestive enzyme activity and body biochemical composition of Labeo rohita fingerlings. A total of 50 Labeo rohita fingerlings were randomly distributed in five treatments including a control group and four experimental groups. Aerva javanica at the rate of 0.5 g, 1.0 g, 1.5 g, 2.0 g were added to the feed. The fish were feed at the rate 4% of their body weight per day for a total period of 60 days. After 60 days the fish samples were analyzed for their growth (Length and weight of fish), digestive enzyme activity (in gut), body biochemical composition (in muscles) (control, exp-1,2,3,4 groups). The results showed significant (p< 0.05) difference in the amount of Amylase, Protease, Lipase, Total Carbohydrate, Protein, Lipids in the treatments compared to the control group at the end of the cultured. The results revealed that the plant powder form of Aerva javanica may act as growth enhancer, digestive enzyme activity, body biochemical composition in the particular level of 1.5 g and 2.0 g in the diet of Labeo rohita fingerlings.